2006
DOI: 10.1111/j.1742-4658.2006.05258.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties and surface activity of surfactant‐like membranes containing the cationic and hydrophobic peptide KL4

Abstract: Surfactant-like membranes containing the 21-residue peptide KLLLL-KLLLLKLLLLKLLLLK (KL 4 ), have been clinically tested as a therapeutic agent for respiratory distress syndrome in premature infants. The aims of this study were to investigate the interactions between the KL 4 peptide and lipid bilayers, and the role of both the lipid composition and KL 4 structure on the surface adsorption activity of KL 4 -containing membranes. We used bilayers of three-component systems [1,2-dipalmitoyl-phosphatidylcholine ⁄ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
53
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 45 publications
(87 reference statements)
8
53
0
Order By: Relevance
“…However, as discussed above, FTIR and CD studies of the structure of KL 4 in lipid environments have led to conflicting results regarding the secondary structure and orientation of KL 4 with respect to a lipid bilayer normal (28-30), possibly due to differences in lipid composition or due to the dependence of these approaches on assumptions regarding secondary structure as well as the solvation status of the peptide backbone. Also, the distribution of the lysines in KL 4 makes its existence as a canonical α-helix on binding to lipids distinctly unfavorable as it would place the charges evenly around the helix rather than making the helix amphipathic (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as discussed above, FTIR and CD studies of the structure of KL 4 in lipid environments have led to conflicting results regarding the secondary structure and orientation of KL 4 with respect to a lipid bilayer normal (28-30), possibly due to differences in lipid composition or due to the dependence of these approaches on assumptions regarding secondary structure as well as the solvation status of the peptide backbone. Also, the distribution of the lysines in KL 4 makes its existence as a canonical α-helix on binding to lipids distinctly unfavorable as it would place the charges evenly around the helix rather than making the helix amphipathic (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Some of this divergence between studies may be due to differences in sample preparation and experimental configuration. A recent investigation utilizing CD to study the effect of peptide: lipid ratios and lipid composition on the structure of KL 4 suggests a helical secondary structure is highly dependent on the presence of negatively charged lipids, such as PG, and fluidity of the membrane (30). Unsaturated lipids decrease bilayer packing density and favor the helical conformation.…”
mentioning
confidence: 99%
“…The above clinical trials indicated that Surfaxin forms a gel in its storage form, and must first be heated to 44°C and then shaken before tracheal administration. The physical basis for this gel formation is not yet known, but may be related to the low binding of KL4 to lipids when compared to native SP-B and SP-C [70], and also to the ability of KL4 to form both β-sheet and α-helix with either mixed lipid monolayers [74] or mixed liposomes at high peptide loading [75]. Such stability problems limited the widespread use of Surfaxin in the treatment of surfactant deficiencies, particularly in emergencies, and have led to the voluntary decision by its producer to withdraw Surfaxin from the market in 2015.…”
Section: Mini-b (Mb) and Super Mini-b (S-mb) Synthetic Peptidesmentioning
confidence: 99%
“…Preparation of Phospholipid Vesicles-Multilamellar vesicles (MLVs) and large unilamellar vesicles (LUVs) were prepared as previously described (34). Briefly, different amounts of DPPC, POPC, or POPG, dissolved in chloroform/methanol (3:1) (v/v), were used alone or mixed to achieve the desired ratios.…”
Section: Methodsmentioning
confidence: 99%